Impedance Matching Network of Passive Coupler with Coaxial Cable for Airborne Sonar Applications (Advances in Military Technology, 2023)
A design methodology is proposed to implement an impedance-matching network in a high-power underwater acoustic transmitting system to minimize power loss through long cables. For this, a Lumped-parameter electrical equivalent circuit model has been developed to analyze the transmitting system along with various couplers and de-couplers introduced for simultaneous transmission of data and DC power along with high-power AC. The effects of these couplers on the end performance of the system have been studied and compensated for by suitably modifying the impedance matching lines (ML). The appropriate impedance matching lines significantly enhance the power by about 300 watts and improve the power factor to 100%.
Keywords: equivalent circuit; impedance matching; Tuning coil; underwater transducer; coupling; airborne sonar